Cardiomiopatia hipertrófica felina: revisão bibliografica - Matteucci, Guilherme [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
Hypertrophic cardiomyopathy (HCM) is the most common heart disease in the feline specie, more frequently affecting pure-breed males such as Ragdolls and Maine Coons. HCM can be primary (idiopathic) or secondary, when other diseases such as hyperthyroidism are involved. The disease is characterized by an increase in the diameter and thickness of the left ventricular wall, with consequent diastolic dysfunction. Mitral regurgitation happens due to compromised ventricular filling, leading to an increased left atrium size and consequent cardiogenic pulmonary edema. Along with the progress of modern veterinary medicine, many diseases could be addressed more successfully on small animal internal medicine, such as feline HCM. This article brings a literature review of the feline hypertrophic cardiomyopathy, focusing on its etiology, physiopathology, clinical presentations, diagnostic methods, therapeutics and prognosis

A cardiomiopatia hipertrófica (CMH) é a afecção cardíaca mais comum nos felinos e tem maior incidência em machos e em animais de raça pura como Ragdolls e Maine Coons, podendo ser primária (idiopática) ou secundária a outras doenças como o hipertireoidismo. A doença se caracteriza por um aumento na espessura e rigidez da parede ventricular esquerda, com consequente disfunção diastólica. A regurgitação mitral ocorre em função do enchimento ventricular comprometido, levando a um aumento atrial esquerdo e consequente edema pulmonar cardiogênico. Com o avanço da medicina veterinária moderna, diversas doenças puderam ser abordadas com maior sucesso na clínica médica de pequenos animais, tais como a CMH felina. A presente revisão tem a intenção de abordar mais profundamente a doença em seus aspectos etiológicos, fisiopatológicos, apresentações clínicas, métodos diagnósticos, terapêutica e prognóstico
Keywords: Miocardio - Doenças; Miocardite; Felideo; Hypertrophic cardiomyopathy; Felines